The effectiveness of pregnancy exercises for a smooth childbirth process - Islami, Thoyibatul; Ismarwati (Majalah Obstetri & Ginekologi, 2025)
HIGHLIGHTS Pregnant women are prone to experiencing labor jams and tears during childbirth Regular pregnancy exercises during the third trimester of pregnancy can help the delivery process run smoothly and reduce the occurrence of birth canal tears.   ABSTRACT Objective: Childbirth is the process of delivering the fetus, placenta, and membranes from the uterus through the birth canal. It requires both physical and psychological preparation to ensure a safe and smooth delivery. This study examined the effectiveness of pregnancy exercises in facilitating a smoother labor process. Materials and Methods: This study employed a systematic review method, utilizing databases such as PubMed, ScienceDirect, ProQuest, Wiley Online Library, and EBSCO. Article selection followed the PICO framework, using keywords like "Prenatal Exercise" OR "pregnant* exercise" AND ("Length of labor" OR "stage* of childbirth") to identify relevant research. Results: Out of 821 articles, 35 were identified as potentially relevant. Various study designs, including retrospective, observational, and experimental studies with control groups, indicated that prenatal exercise can not only facilitate a faster labor process but also accelerate postpartum involution and positively impact maternal and infant health. However, some cohort studies reported conflicting findings, showing no significant relationship between prenatal exercise and labor outcomes. These discrepancies may be attributed to factors such as maternal health status, prior childbirth experience, and the type and intensity of prenatal exercise performed. Conclusion: The reviewed articles indicate that prenatal exercise significantly facilitates and optimizes the labor process. Therefore, it is essential to encourage pregnant women to engage in regular prenatal exercise starting in the third trimester, ensuring it is conducted safely and comfortably to maximize its benefits for both mother and baby.